Multilevel analysis of hemodialysis-associated infection among end-stage renal disease patients: results of a retrospective cohort study utilizing the insurance claim data of Fukuoka Prefecture, Japan - Jamal, Aziz (Medicine (Baltimore), 2020)
The presence of comorbid conditions along with heterogeneity in terms of healthcare practices and service delivery could have a significant impact on the patient's outcomes. With a strong interest in social epidemiology to examine the impact of health services and variations on health outcomes, the current study was conducted to analyse the incidence of hemodialysis-associated infection (HAI) as well as its associated factors, and to quantify the extent to which the contextual effects of the care facility and regional variations influence the risk of HAI. A total of 6111 patients with end-stage renal disease who received hemodialysis treatment between 1 October 2015 and 31 March 2016 were identified from the insurance claim database as a population-based, close-cohort retrospective study. Patients were followed for one year from April 1, 2016 to March 31, 2017. A total of 200 HAI cases were observed during the follow-up and 12 patients died within 90 days of the onset of HAI. Increased risks for HAI were associated with moderate (HR 1.73, 95% confidence interval [CI] 1.00–2.98) and severe (HR 1.87, 95% CI 1.11–3.14) comorbid conditions as well as malignancy (HR 1.36, 95% CI 1.00–1.85). Increased risk was also seen among patients who received hemodialysis treatment from clinics (HR 2.49, 95% CI 1.1–5.33). However, these statistics were no longer significant when variations at the level of care facilities were statistically controlled. In univariate analyses, no statistically significant association was observed between 90-day mortality and baseline patients, and the characteristics of the care facility. The results of the multivariate, multilevel analyses indicated that HAI variations were only significant at the care facility level (σ(2) 2.07, 95% CI 1.3–3.2) and were largely explained by the heterogeneity between care facilities. The results of this study highlight the need to look beyond the influence of patient-level characteristics when developing policies that aim at improving the quality of hemodialysis healthcare and service delivery in Japan.